Penerapan Manajemen Berbasis Digital Dalam Peningkatan Layanan Akademik Di SMA Negeri 2 Luwu - Putri Nabila; Taqwa; Firman Patawari; Tasdin Tahrim (Hikamatzu | Journal of Multidisciplinary, 2024)
This journal discusses digital-based management in improving academic services at SMA Negeri 2 Luwu. This study aims to determine how academic services at SMA Negeri 2 Luwu and the application of digital-based management in improving academic services at SMA Negeri 2 Luwu. The type of research used in this research is descriptive qualitative. Data sources consist of primary data and secondary data, with data collection techniques consisting of observation, interviews, and documentation. Data analysis was carried out with three stages, namely data reduction, data presentation, and conclusion drawing. The results showed that academic services at SMA Negeri 2 Luwu have met the Minimum Service Standards (SPM) of the national education sistem organizers of the Ministry of Education and Culture in 2003. In its implementation, academic services at SMA Negeri 2 Luwu include managing facilities and infrastructure to support the teaching and learning process, managing activities in schools, procuring and managing all administration at SMA Negeri 2 Luwu. Starting from the admission of new students, class / major division, teaching curriculum, attendance, facilitating the learning process, supporting teachers' needs for teaching needs both property and information. Academic services are also carried out for alumni in the form of diploma management both issuance, attestation, and other services. And the application of digital-based management in improving academic services at SMA Negeri 2 Luwu consists of: 1) One Stop Integrated Service, 2) PPDB (New Student Admission), 3) Online Learning. And 4) Digital report card. To accommodate the implementation of digital-based management in improving academic services, SMA Negeri 2 Luwu provides supporting facilities such as computers, wifi, giving permission for students to bring smartphones and leptops to school, providing Digital Smart Tvs, LCD Projectors, and other electronic devices..